The operational validity of a video-based situational judgment test for medical college admissions: Illustrating the importance of matching predictor and criterion construct domains - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2005)
This study is part of a trend of examining noncognitive predictors, for example, a situational judgment test (SJT), as supplements to cognitive predictors for making college admission decisions. The authors examined criterion data over multiple academic years and universities. The criterion domain was broadly conceptualized, including both cognitive and interpersonal domains. The sample consisted of 7,197 candidates of the Medical and Dental Studies Admission Exam in Belgium. Results confirmed the importance of cognitive predictors. A video-based SJT was differentially valid for predicting overall grade point average for different curricula. The SJT showed incremental validity over cognitively oriented measures for curricula that included interpersonal courses, but not for other curricula. The SJT became more valid through the years. This demonstrates the importance of carefully specifying predictor-criterion linkages and of differentiating both predictor and criterion constructs.